Peran Rekam Kesehatan Elektronik dalam Meningkatkan Efisiensi dan Mutu Pelayanan di Puskesmas Pejeruk - Rizal Pratama Adi Putra; Uswatun Hasanah; Musparlin Halid; Beny Binarto Budi Susilo; Rian Wahyul Ikhtiar; Rizal Fikri (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study stems from the need for digital transformation in the health sector to improve the quality of services that are effective, fast, and safe. This study aims to analyze the implementation of Electronic Health Records (EHR) in improving the efficiency and quality of services at the Pejeruk Community Health Center, Mataram. The research method used was a quantitative approach with a correlational analytical design, using Spearman's correlation test to determine the relationship between the variables of EHR, efficiency, service quality, and patient satisfaction. Data were collected through questionnaires filled out by health workers and patients who interacted directly with the EHR system. The results showed that there was no significant relationship between the implementation of EHR and efficiency (r = -0.071; p = 0.676), service quality (r = -0.057; p = 0.737), or patient satisfaction (r = -0.071; p = 0.676). However, there was a significant relationship between efficiency and service quality (r = -0.367; p = 0.026), indicating a negative influence between increased efficiency and service quality. These findings indicate that the implementation of RKE at the Pejeruk Community Health Center is still in the adaptation stage, so it has not had an optimal impact on improving service quality and efficiency. Based on these results, it is recommended that training on the use of RKE for health workers be improved, digital infrastructure be upgraded, and continuous evaluation be conducted to optimize the benefits of the health information system in supporting quality services.